Are private investors willing to pay for sustainable investments? A stated choice experiment - Gunnar Gutsche; Andreas Ziegler (Philipps-University Marburg, School of Business and Economics, 2016)
This paper examines the willingness of private financial decision makers to pay for socially responsible investments (SRI). Our empirical analysis is based on unique data from a representative computer-based survey in Germany that especially comprised two stated choice experiments. The experiments referred to choices among several equity funds and among several three-year fixed-interest investment products and especially comprised sustainability criteria and financial performance indicators as main attributes. Our econometric analysis with mixed logit models reveals strong stated preferences and thus a considerable willingness to pay for sustainable investments. For example, the estimated mean willingness to sacrifice yearly nominal interest rates for sustainable fixed-interest investment products amounts to 0.21 percentage points among a variation between 1.30% and 2.10%. These results are very stable across several robustness checks that also include different techniques to mitigate possible hypothetical biases. Our latent class logit model analysis confirms a high extent of unobserved heterogeneity between different investor groups and especially reveals that specific social values and norms play an important role. Investor groups with strong considerations of norms by the social environment with respect to SRI and especially with high feelings of warm glow from SRI, a strong environmental awareness, and an affinity to left-wing parties have a substantially higher estimated mean willingness to pay for sustainable investments.
Keywords: G11; Q56; M14; G02; A13; C25; 330; socially responsible investments; stated choice experiments; mixed logit models; latent class logit models; willingness to pay; social values and norms